Value migration: Digitalization of shipping as a mechanism of industry dethronement - Konstantinos Poulis; Gregorios C. Galanakis; Gregory T. Triantafillou; Efthimios Poulis (Journal of Shipping and Trade (JST), 2020)
In this conceptual paper, we review latest developments related to unmanned vessels and sketch potential scenarios that implicate with the existing maritime industry structure. On the one hand, we isolate a range of challenges that make the imminent realization of unmanned vessels seem like a rather utopian pursuit. On the other hand, we explain the reasons that may catalyse their emergence. Inspired by these opposing tensions, we highlight that the digital transformation of the shipping industry has the potential to enhance value within the industry's ecosystem. However, we also contend that unmanned vessels -if realized- pose a very particular threat to the identity of the shipping industry as we know it. In particular, we build upon the concept of value migration and we highlight the drastic existential changes that may likely stem from a shift to non-seafarer-centric shipping. We conclude with questions that matter for industry dethronement purposes i.e., the possibility that existing industry structures may be substantially reconfigured following a removal of the seafarer as the nucleus of value creation in shipping.
Keywords: 650; Unmanned vessels; Crew; Value migration; Digitalization; Industry dethronement; Autonomous operations